Primary mucoepidermoid carcinoma at the carina of trachea presenting with wheezing in an asthmatic child mimicking an attack of asthma: A case report. Issue 44 (November 2016) - Lin, Chien-Heng; Chao, Yu-Hua; Wu, Kang-Hsi; Lin, Wei-Ching
Abstract: Background: Asthma is a very common disease, but primary tracheal tumors are extremely rare in children. Wheezing is not pathognomonic, but is the typical presentation of asthma and could also be found in patients with tracheal tumors. Clinical Findings: This report describes a 12-year-old boy with a previous history of frequent asthma attacks and experienced responses to antiasthma treatment. He was admitted to the hospital due to persistent wheezing and progressive dyspnea. Hyperinflation in the bilateral lungs was detected on chest x-ray, but without other significant findings. Chest computed tomography revealed a mass at the carina. Tracheal mucoepidermoid carcinoma was diagnosed by histopathological assessment. Conclusion: Despite the rarity of tracheal tumors, chest computed tomography scans should be performed in the first place for children presenting persistent wheezing and having poor response to antiasthma treatment to rule out the other alternative diagnosis. Coexistence of other diseases such as tracheal tumor in asthmatic patients should be considered.